L'adquisició infantil de les llengües de signes - Quer, Josep (Caplletra. Revista Internacional de Filologia, 2003)
This article offers an overview of research in sign language acquisition by children, mostly in American Sign Language. The results indicate that the developmental milestones and the linguistic errors made by children acquiring a sign language coincide with those observed in hearing children acquiring spoken languages. The visual-gestural modality is shown not to have the expected impact on the acquisition processes, which is arguably regulated by strictlylinguistic principles.